La fiesta: utopía, historia y derecho a la vida - Salinas Campos, Maximiliano (Revista de Historia Social y de las Mentalidades, 2011)
This paper attempts an historiological approach to the feast. How can this subject be introduced as an historical purpose? The West Ìs intellectual and material world, especially in its bourgeois determinations, leads to a denial of this topic. Western historicity thinks of itself from the logics of conquest, exploitation, and rationalization of the world. These logics find their natural conclusion in the right to kill the Earth. A reflection on the feast seeks to reverse such logics in order to reencounter the right to life on Earth. It is here that the question of the historical character of the Feast find its ultimate sense. The feast place us on the tracks of the origins, subsistence and purpose of life onEarth. This must be seen from the angle of the recovery of the image of Dionysos, conceived as the archetype of indestructible life